A CASE- CONTROL STUDY ON PROSTATE CANCER INRURAL POPULATION OF PAKISTAN - Muhammad Naeem Bashir; Muhammad Akram Malik; Muhammad Riaz Ahmad (Journal of University Medical & Dental College, 2015)
ABSTRACT BACKGROUND: As in many countries of the world, Prostate cancer is extremely common in Pakistan. It is the third most common malignancy among males in Pakistan. A hospital-based, case-control study was conducted in rural area of Faisalabad (Pakistan) to examine the probable risk factors of prostate cancer. MATERIALS AND METHODS: This study was based on 102 prostate cancer cases and 204 normal controls. Logistic regression was used to estimate odds ratios and 95% conﬁdence intervals to evaluate the relationship between prostate cancer and different risk factors. RESULTS: Age, family history of prostate cancer and obesity signiﬁcantly increased the prostate cancer risk having odds ratios and 95% conﬁdence interval (13.56; 5.20-35.35), (4.70;1.6513.40) and (4.26; 2.25- 8.10) respectively. On the other hand, better lifestyle (physical activity) and literacy signiﬁcantly decreased the prostate cancer risk having odd ratiosand corresponding 95% conﬁdence intervals (0.16; 0.08- 0.30)and (0.32; 0.15- 0.65) respectively. CONCLUSIONS: In the present study age, family history of prostate cancer, obesity, literacy and better lifestyle emerged as risk factors for prostate cancer in rural population of Faisalabad